Characterization of Symptoms after Radical Prostatectomy and Their Relation to Postoperative Complications. Issue 2 (21st February 2022) - Clements, Matthew B.; Tin, Amy L.; Estes, Connie L.; Jibara, Ghalib; Desai, Priyanka K.; Ehdaie, Behfar; Touijer, Karim A.; Scardino, Peter T.; Eastham, James A.; Assel, Melissa J.; Vickers, Andrew J.; Simon, Brett A.; et al.
Abstract : Purpose: Many patients will experience symptoms in the initial days after radical prostatectomy (RP), but early patient-reported symptoms have not been well characterized. Our objective was to illustrate the pattern of symptoms experienced after RP and the relation of severe symptoms to postoperative complications. Materials and Methods: In 2016, electronic patient-reported symptom monitoring began at our institution's ambulatory surgery center. We retrospectively reviewed patients treated with minimally invasive RP who were sent a daily questionnaire completed using a web interface until postoperative day 10. Severe symptoms automatically generate a "yellow alert, " which messages the clinic, while very severe symptoms generate a "red alert, " additionally prompting the patient to call. We summarized rates of moderate-to-very severe symptoms and fit local polynomial regressions. We compared rates of 30-day or 90-day complications (grade ≥2) based on the presence of alert symptoms. Results: Of 2, 266 men undergoing RP, 1, 942 (86%) completed surveys. Among moderate-to-very severe symptom levels, pain (72%) and dyspnea (11%) were most common. Pain, nausea and dyspnea consistently decreased over time; fever and vomiting had a flat pattern. In patients experiencing red-alert symptoms, we observed a higher risk of 30-day complications, but rates were low and differences between groups were nonsignificant (2.9% vs 1.9%; difference 1.1%; 95% CI −1.3–3.5; p=0.3). Results were similar examining 90-day complications. Conclusions: While symptoms are common after RP, substantial improvements occur over the first 10 days. Severe or very severe symptoms conferred at most a small absolute increase in complication risk, which should be reassuring to patients and clinicians.